The development of a novel technique for AFM thermal analysis of individual phases in polymer mixtures after separation and identification via LC-FTIR - De Goede, E. (Elana) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2004.